Subclinical Diabetes - LUÍS M.T.R. LIMA (Anais da Academia Brasileira de Ciências)
ABSTRACT Type 2 diabetes mellitus (T2DM) is increasing in prevalence worldwide, and those non-diagnosed or misdiagnosed comprise a significant group compared to those diagnosed. Accumulated scientific evidence indicate that the current diagnostic markers (fasting glycemia, 2h glycemia after an oral glucose load and HbA1c) are indeed late diagnostic criteria when considering the incidence of diabetes-related complications and comorbidities, which are also at high risk in some groups among normoglycemic individuals. Additionally, the earlier identification of future risk of diabetes is desirable since it would allow better adherence to preventive actions such as lifestyle intervention, ultimately avoiding complications and minimizing the economic impact/burden on health care expenses. Insulin resistance and hyperhormonemia (insulin, amylin, glucagon) are non-disputable hallmarks of T2DM, which already takes place among these normoglycemic, otherwise health subjects, characterizing a state of subclinical diabetes. Insulin resistance and hyperinsulinemia can be computed from fasting plasma insulin as an independent variable in normoglycemia. An overview of the current diagnostic criteria, disease onset, complications, comorbidities and perspectives on lifestyle interventions are presented. A proposal for early detection of subclinical diabetes from routine evaluation of fasting plasma insulin, which is affordable and robust and thus applicable for the general population, is further suggested.